Intraductal carcinoma of the prostate is an aggressive form of invasive carcinoma and should be graded - Samaratunga, Hemamali; Delahunt, Brett; Egevad, Lars; Srigley, John R.; Billis, Athanase; Bostwick, David G.; Camparo, Philippe; Cheng, Liang; Clouston, David; Denham, James; Furusato, Bungo; Hartmann, Arndt; et al. (Pathology, 2019)
Infiltration of the prostatic ducts by prostatic adenocarcinoma occurs relatively frequently, being most commonly associated with high grade disease. It is now recognised that intraductal carcinoma of the prostate (IDCP) has an associated poor prognosis and this is reflected in its histological, molecular and immunohistochemical features. The current recommendation of the World Health Organization is that IDCP not be taken into consideration when grading prostate adenocarcinoma. It is apparent that Gleason did not differentiate between IDCP and stromal invasive carcinoma when developing and validating his grading system, and recent studies suggest that the incorporation of IDCP grading into the overall grading of the specimen provides additional prognostic information.
CRIS-Team Scopus Importer:2019-12-27
Keywords: intraductal carcinoma of prostate; ISUP grade; prognosis; Prostate adenocarcinoma